Afghanistan Development Update, October 2016 - World Bank (World Bank, Washington, DC, 2016)
Security and development remain inextricably linked in Afghanistan, with the poor security environment continuing to exert a significant constraint on confidence, investment, and growth. As a result, in 2015, the economy grew at only 0.8 percent. In addition to the security situation, adverse weather conditions also constrained growth, contributing to a decline in agricultural production of 5.7 percent in 2015. Available data for the first half of 2016 indicate ongoing low levels of investment, with agricultural production expected to remain poor due to crop diseases and pests. Thus, in 2016, the growth rate is expected to reach only 1.2 percent, despite progress with a number of important initiatives that are expected to have a positive impact on Afghanistan’s economic development, including Afghanistan’s accession to the World Trade Organization and the opening of the Chabahar port in Iran. With the economic growth rate significantly lower than the population growth rate, it is expected that poverty will have increased in 2015 and that it is likely to continue to increase throughout 2016. In the medium-term future, economic growth is expected to gradually accelerate, increasing from 1.8 percent in 2017 to 3.6 percent in 2019. However, stronger growth in out-years is predicated on improvements in security, political stability, reform progress, and continued high levels of aid.